State intervention in the unions, labor laws and labor movement situation through brochures and reports from the Dirección General del Trabajo (1925) - Mellado Carrasco, Vicente (Cuadernos de Historia, 2022)
Documentation here presented are selected reports and brochures from volume 100 and 101 (year 1925) taken from Fondo de la Dirección General del Trabajo, located in Archivo Nacional de la Administración (ARNAD) in Santiago, Chile. The brochure corresponds to a brief Law 4057 instruction from Trade Union Organization to be disseminated among the nitrate office’s workers from the Antofagasta Province; then, in chronological order are presented, a report of the Inspección Regional del Trabajo (IRT) from Valparaíso dated in June 1925; an extract from an IRT report from Concepción from June, and finally a brief report from July 1925; reports describe the labor movement’s current state, its labor laws reception and its ideological leanings. Finally, a record from industrial unions quantity (22) and a constituted directories list in Antofagasta province until August 1925 are presented.